Biocontrol of Macrophomina phaseolina (Tassi) Goid causing charcoal rot disease in Lycopersicon esculentum L. by using multi species bacterial consortia - Kumar, Pradeep; Kumar, Sandeep; Dubey, R.C. (Environment conservation journal, 2021)
Plant growth-promoting bacterial strains (LEP1-LEP31) were isolated from rhizosphere of Lycopersicon esculentum L. (Tomato) and screened for their plant growth promoting (PGP) activities. On the basis of morphological, physiological, biochemical, carbon source utilization and molecular characterization, these strains were identified as Pseudomonas sp., Azotobacter sp. and Bacillus sp. For antagonistic activities all the strains were subject to the chitinase activities by the development of clear halo around the inoculated bacterial spots when loaded on chitin (0.2%) supplemented mediumBased on pot and field trial results of individual strains and consortium application, it may be concluded that all the three strains i.e. Pseudomonas sp. LEP17, Azotobacter sp. strain LEP21 and Bacillus sp. strain LEP25 showed plant growth promoting effects. The growth promotion provided by these strains was apparently related to improve shoot and root development, which resulted in better nutrient uptake capability and suppression of plant pathogen. All these three strains were superior in this regard because they provided the best and most consistent effects on growth and yield of L. esculentum. All these strains Pseudomonas sp. LEP17, Azotobacter sp. strain LEP21, Bacillus sp. strain LEP25 and their consortium seems to be suitable for use as a plant growth promoting and improvement of growth and yield